A Case of Precocious Puberty in a Setting with Limited Resources - Paudel, K P; Giri, S; Shrestha, P S; Shrestha, L; Thapa, S B; Shrestha, M (Kathmandu University Medical Journal, 2012)
Precocious puberty is a rare condition characterized by the development of secondary sexual characteristics before the median age for the sex. It is either gonadotropin dependent also called as central or gonadotropin independent also known as peripheral type. Hypothalamamic Hamartoma is a common cause of the central or precocious puberty due to organic brain lesion. Here we present a two year male who presented us with precocious puberty due to a hypothalamic Hamartoma. DOI: http://dx.doi.org/10.3126/kumj.v9i4.6353 Kathmandu Univ Med J 2011;9(4):315-7